Catar folhas e contar o tempo: antirracismo e racismo religioso nos discursos de Mestres de Axé - Melina Sousa da Rocha (2019)
This study, namedCatar folhas e contar o Tempo: antirracismo e racismo religioso nos discursos de Mestres de Axé, investigated the speeches of the masters in traditional Afro religious knowledge, who taught the discipline Catar Folhas: Saberes e Fazeres do povo de axé, offered for the transversal formation in Traditional Knowledge of UFMG, in the year 2017. The study presents a debate about racism and anti-racism, having as perspective the religious racism in the educational experiences of the masters. Through interviews and transcriptions, the discourse analysis method was adopted, seeking to understand the meanings given by these subjects to these experiences. There was a need to carry out a bibliographic survey that could assist in understanding the space for training these teachers. In this sense, we reflect on black religious spaces as spaces for socialization and the production of anti-racist knowledge. The study brought historical aspects, and studies of culture to define what afro religious knowledge is, understanding that the place of discourse also shapes social places in our society. Through the analysis it is possible to verify how religious racism promotes violence to the subjects, as well as anti-racism, or discourses against colonials are established as new epistemologies.